Functioning and Control of Phagocytosis - Turyamuhika, Laban; Agaba, Bosco; Asiimwe, Moses; Musinguzi, Benson; Okek, Erick (IntechOpen, 2023)
Phagocytosis is a very complex and versatile process that contributes to immunity through a series of events that is it’s sometimes referred to the Come and Eat me process. Due to the recognition ingestion and digestion then destruction. It’s also central to tissue homeostasis and remodeling by clearing dead cells. This ability of phagocytes to perform such diverse functions rests in large part on their vast repertoire of receptors. In this book chapter we looked at the processes used by phagocyte to perform there phagocytosis function. This is made possible by the binding of opsonins on the microbes like the C3b of the complement. This works as a chemo attractant to the phagocytes to come and initiate the process of eating. On recognition this microbe or dead cell interacts with the phagocyte with the help of a very big repertoire of receptors the microbe is engulfed with in the phagosome. As microbes interact with the phagocyte receptors a cascade of signaling events downstream that then activate phagocytosis. This membrane and cytoskeleton remodulation lead to the formation of pseudopods that cover the entire microbe forming a phagocytic cup which closes a few minutes to take up the microbe completely. The signal cascade is most known for the Fc receptor activities. Crosslinking of the Fc receptor on the surface of phagocyte activate phagocytosis and any other effector functions such as activation of the oxidative burst, degranulation, antibody dependent cell mediated cytotoxicity and activation of genes for cytokine/chemokine production that are beneficial in microbe destruction and initiation of inflammation. This starts once the interaction of phagocytes receptors and their ligands on the target microbes takes place appropriately. The phagocyte receptors will then aggregate to activate a series of pathways that regulate actin cytoskeleton which helps in the formation of a new vesicle which comes out of the membrane to enclose the microbe. In here a number of processes and stages take place all aimed at killing and denaturing the particle. They include early phagosome, intermediate phagosome, phagolysosome formation and the late phagosome all these participate in eliminating the phagocytized microbe. However with all the above phagocytic efficiency, some pathogens evade phagocytosis using different means and presence of certain capacities that facilitate evasion examples of organisms that evade phagocytosis include Mycobacterium tuberculosis, Listeria monocytogens Escherichia coli etc. all these use different means in evasion. Therefore the concept and science of Phagocytes used to be studied more to explore more pharmaceutical products based on the evasion mechanisms.